Real-world effectiveness and tolerability of erenumab: A retrospective cohort study. (November 2020) - Kanaan, Saad; Hettie, Gabrielle; Loder, Elizabeth; Burch, Rebecca
Background: We aimed to systematically assess the effectiveness and tolerability of erenumab in a clinical setting, specifically a tertiary headache center. Methods: This was a retrospective cohort study at the John Graham Headache Center of Brigham and Women's Hospital. All patients who received erenumab from a headache specialist at the Center from 17 May 2018 to 31 January 2019 were included. Patients were contacted and underwent a structured clinical interview including information about erenumab use, perceived benefit, adverse events (AEs), and a global assessment of benefit versus drawbacks. Chart review was performed for patients who could not be contacted. Results: Four hundred and forty-four patients were initially identified and 418 were eligible. Two hundred and ninety-five participants completed the structured clinical interview portion of the study (response rate 70.6%). Seventy-four patient charts were additionally reviewed. Two hundred and forty-one participants had used erenumab. One hundred and sixty nine (70%) of participants experienced at least one adverse event, with constipation (43%), injection site reaction (24%), fatigue (15%), worsening headache (12%), and dizziness (11%) the five most commonly reported AEs. One hundred and sixty-eight participants (69.7%) felt that the benefits of erenumab outweighed any drawbacks. One hundred and fifty-one participants (62.7%) planned to continue using erenumab. Cost of treatment was cited by 12% of participants as a reason for either not starting or for stopping erenumab. Of patients who had an increase in dose due to lack of or partial efficacy, 46.5% felt that the dose increase was helpful. We identified one case of unintended pregnancy in our study population. Conclusions: This large "real-world" study validates the findings of benefit of erenumab observed in clinical trials. Although adverse events were far more common in this population than in clinical trials, the planned continuation rate was relatively high. The substantial discrepancy between adverse events seen in clinical practice compared with clinical trials suggests systematic differences between clinical trial participants and patients who receive the treatment in clinical practice, or may indicate suboptimal ascertainment of adverse events in the trials. Clinicians should continue to be vigilant for adverse events in clinical practice.